Pembelajaran outdoor study dalam mata pelajaran Geografi: Systematic review - Siti Azizah Susilawati; Salma Lutfiani Sochiba (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2022)
Learning Geography in the classroom is less effective, so learning strategies are required. The outdoor study strategy is a type of learning strategy in which teaching and learning activities take place outside of the classroom. The purpose of this systematic review is to identify outdoor study learning in Geography in high school. This is a qualitative study using a systematic review method. Narrative analysis is used in this research design. The findings of a study on outdoor study learning in Geography subjects at the high school level have been widely applied to environmental and sustainable development materials, which were obtained in 7 journals (29 percent), and based on the research findings measured variables related to outdoor studies, namely learning outcomes, which were obtained in 19 journals (79 percent). Based on the findings of this systematic review, it is possible to conclude that the outdoor study strategy can be used at all levels of education. Furthermore, the outdoor study strategy can increase activity, enthusiasm, motivation, responsibility, respect for others, care for the environment, make it easier for students to understand the material, and improve learning outcomes. learners.Pembelajaran Geografi kurang efektif jika dilakukan di dalam kelas sehingga membutuhkan strategi pembelajaran. Strategi outdoor study merupakan suatu strategi pembelajaran dimana kegiatan belajar mengajar dilakukan diluar kelas. Penelitian systematic review ini bertujuan untuk mengidentifikasi pembelajaran outdoor study dalam mata pelajaran Geografi di SMA. Penelitian ini merupakan penelitian kualitatif dengan metode systematic review. Desain penelitian ini menggunakan analisis naratif. Hasil penelitian pembelajaran outdoor study dalam mata pelajaran Geografi di jenjang SMA banyak diterapkan pada materi lingkungan hidup dan pembangunan berkelanjutan diperoleh 7 jurnal (29 persen), dan berdasarkan variabel hasil penelitian yang diukur terkait outdoor study yaitu hasil belajar diperoleh 19 jurnal (79 persen). Berdasarkan systematic review ini dapat disimpulkan bahwa strategi outdoor study dapat diterapkan pada semua tingkat satuan pendidikan selain itu, melalui strategi outdoor study dapat meningkatkan keaktifan, semangat, motivasi, tanggung jawab, menghargai sesama, peduli lingkungan, memudahkan siswa memahami materi, dan meningkatkan hasil belajar peserta didik.